Functional genomics identifies neural stem cell sub-type expression profiles and genes regulating neuroblast homeostasis. - Carney, T.D.; Miller, M.R.; Robinson, K.J.; Bayraktar, O.A.; Osterhout, J.A.; Doe, C.Q. (Developmental Biology, 2012)
The Drosophila larval central brain contains about 10,000 differentiated neurons and 200 scattered neural progenitors (neuroblasts), which can be further subdivided into ~95 type I neuroblasts and eight type II neuroblasts per brain lobe. Only type II neuroblasts generate self-renewing intermediate neural progenitors (INPs), and consequently each contributes more neurons to the brain, including much of the central complex. We characterized six different mutant genotypes that lead to expansion of neuroblast numbers; some preferentially expand type II or type I neuroblasts. Transcriptional profiling of larval brains from these mutant genotypes versus wild-type allowed us to identify small clusters of transcripts enriched in type II or type I neuroblasts, and we validated these clusters by gene expression analysis. Unexpectedly, only a few genes were found to be differentially expressed between type I/II neuroblasts, suggesting that these genes play a large role in establishing the different cell types. We also identified a large group of genes predicted to be expressed in all neuroblasts but not in neurons. We performed a neuroblast-specific, RNAi-based functional screen and identified 84 genes that are required to maintain proper neuroblast numbers; all have conserved mammalian orthologs. These genes are excellent candidates for regulating neural progenitor self-renewal in Drosophila and mammals.